Coastal processes : with engineering applications - Dean, Robert G. (Robert George), 1930-2015 (Cambridge University Press, 2002)
This text is organized in four parts: (1) an overview of coastal engineering, using case studies to illustrate problems; (2) hydrodynamics of the coastal zone, reviewing storm surges, water waves, and low frequency motions within the nearshore and surf zone; (3) coastal responses including equilibrium beach profiles and sediment transport; (4) applications such as erosion mitigation and shoreline management.